Persistent Sciatic Artery Aneurysm with Lower Limb Ischemia. (10th February 2014) - Kesri, Gaurav; Mangtani, Jitendra; Kumar, Gaurav; Dangayach, Krishan Kumar
Abstract : Persistent sciatic artery is a very rare clinical entity. Those of us who have not seen the lesion regard this as a condition which is described in the literature through less than 200 cases. We report, here, a case of a 60-year-old female who presented to the surgical outdoor with complaints of a pulsatile gluteal swelling associated with ischemic changes in the ipsilateral lower limb. On Doppler and CT angiographic analysis, the patient was determined as having persistent sciatic artery aneurysm which was then managed by a combined surgical and endovascular approach. Ours is probably the first such case to be reported from India. The objective of this case report is to highlight the relevant embryology, the pathognomonic presenting features, the diagnostic dilemma, management, and complications associated with a case of persistent sciatic artery (PSA).